نظرية الأهلية: دراسة تحليلية مقارنة بين الفقه وعلم النفس (Nazariyah al-ahliyah: dirasah tahliliyah muqaranah bayn al-fiqh wa-'ilm al-nafs) - Hilal , Huda Mohammad Hassan (The International Institute of Islamic Thought, 2011)
This study attempts to formalize a theory for Qualification based on modern psychology science. Such theory resolves many of juristic disagreements and modern issues related to Qualification. This requires researching the gap between old transcripts on one hand and modern studies in Psychology and Islamic jurisprudence on the other hand. The study adopts an analytical inductive methodology through the analysis of juristic books, psychology literature, and uses deductive reasoning in stating logical findings. The study yields a number of results. Firstly, the gap in juristic literacy in Qualification studies appears in three aspects. The lack of reference to psychology which is considered the knowledge background, the lack of attempts to formalize a comprehensive theory, and the lack of efforts to expand the circle of juristic research in related issues. The study reaches to the reasons of this gap. Firstly, the lack of work made that revises the conceptions exhibited by early jurists. Secondly, the isolation of juristic studies from the impacts of technology on Islamic legal rulings. Thirdly, the disregard of professional studies in related juristic issues. These reasons lead to a number of consequences. Firstly, misunderstanding and discrepancies in some of the juristic concepts. Secondly, preservation of some of the terminologies that faded as a result of civil advancement. Thirdly, the inability to create a tool that measures the Qualification of a legally commissioned person in a specific stage in his/her lifespan and that is capable to specify the legal ruling for any legal incidental excuse. Fourthly, the inability to find the legal ruling in juristic issues of Qualification related to scientific studies. The study suggest a number of means to overcome this gap based on the principal idea of Qualification; that is, the fact that a human being develops through stages in three dimensions, physical brain, cognition, and moral. These developments through stages result in variant legal rulings. By comparing between these stages in Islamic jurisprudence and developmental psychology, the basis of the Qualification theory can be made. Firstly, relating major Qualification issues to the respective psychological researches. This is done by, firstly, tracing the development of brain and nervous system, cognition and via the sequential developmental stages. Secondly, by trying to invent a real measure to control the Qualification by reading the biological signs, and changes with the respective legal rulings. This leads to the identification of five stages of Qualification; embryology and early childhood, middle childhood, puberty, early adulthood, late adulthood and death. Thirdly, formulating a theory for Qualification. The conditions of this theory are humanity, mind, merit, and physical ability. The pillars are human being, duties and obligations, and the law givers. Fourthly, mentioning the different juristic opinions in juristic issues pertaining to Qualification. Fifthly, considering biological studies as scientific evidences in such issues. Sixthly, independent judgment in juristic issues for Qualification through re-understanding the evidences from Quran and Prophet Tradition, and matching contemporary psychological illnesses to their alike through analogical deduction